Does cryotherapy before drainage increase the risk of intraocular haemorrhage and affect outcome?: A prospective, randomised, controlled study using a needle drainage technique and sustained ocular compression. Issue 7 (1st July 1997) - Pearce, I A; Wong, D; McGalliard, J; Groenewald, C
Abstract : AIMS/BACKGROUND: A prospective, randomised, controlled clinical trial was conducted to investigate the effect of performing cryotherapy before drainage of subretinal fluid (SRF) on the incidence of intraocular haemorrhage (IOH) in the management of retinal detachment. METHODS: Eighty eyes of 80 patients with rhegmatogenous retinal detachment requiring SRF drainage were recruited. Thirty four cases were randomised to receive drainage before cryotherapy (drainage, air injection, cryotherapy, and explant = DACE group) while 46 cases had drainage after cryotherapy (cryotherapy, drainage, air injection, and explant = CDAE group). All cases had trans-scleral drainage of SRF using a 27 gauge hypodermic needle combined with prolonged, intraocular hypertension. RESULTS: There was a low incidence of IOH associated with drainage in both groups with no statistically significant difference between the groups (DACE group = 2.9%; CDAE group = 4.3%; p = 0.43). There was no significant difference between the groups in the rate of anatomical success with a single operation (DACE group = 82.4%; CDAE group = 86.9%; p = 0.38). There was no significant difference between the groups in the visual outcome. An improvement of two Snellen lines or more occurred in 52.9% of the DACE group and in 56.5% of the CDAE group (p = 0.93). CONCLUSION: It was concluded that the surgical sequence of applying cryotherapy before drainage of SRF can be safely and effectively performed. The sequences CDAE and CDE, when air injection is not required, along with DACE should all be part of the surgical repertoire for the management of retinal detachments.